Pengembangan Media Slide Show Power Point by Using Audio Effect Terhadap Pemahaman Konsep Matematika - Riswari, Lovika Ardana; Ermawati, Diana; Evanita, Evanita (WASIS : Jurnal Ilmiah Pendidikan, 2025)
This research aims to develop a Slide Show PowerPoint learning media enhanced with audio effects to support students' understanding of mathematical concepts, particularly in the area of circle measurement.The method used is the Research and Development (R&D) approach with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The instruments in this study include validation sheets, practicality sheets, and effectiveness sheets. The validation sheet assesses the validity of the media based on input from experts regarding text, images, audio, and its suitability to the subject matter. The practicality sheet uses a questionnaire to obtain student responses regarding the clarity of text, images, presentation of material, and ease of use of the media. Meanwhile, the effectiveness sheet is used to measure differences in student understanding through a pretest before using the media and a posttest. The data analysis used in this study is a feasibility test in the form of a validity test by media experts with scoring guidelines using a Likert scale.The results of the study indicate an increase in students' understanding of mathematical concepts; 73% of students achieved a high category with scores above the minimum competency standard (KKTP). Additionally, 90% of students reported that the media was worthy to use, helped in understanding concepts. These results demonstrate that technology-based media, such as Slide Show PowerPoint with audio effects, is effective in enhancing students' understanding and interest in mathematics learning